2000
DOI: 10.1007/bf02491567
|View full text |Cite
|
Sign up to set email alerts
|

Separation of phenolic acids in soil and plant tissue extracts by co-electroosmotic capillary electrophoresis with direct UV detection

Abstract: A capillary zone electrophoretic method for the analysis of phenolic acids in soil and plant extracts was developed with direct UV detection using a phosphate electrolyte solution. The electrophoretic separation required the phenolic acids to be charged at a pH above their pKa in order to achieve their migration towards the anode. Electroosmotic flow (EOF) was reversed in direction by adding tetraclecyhrimethylammonium bromide (gAB). Factors affecting the separation selectivib,, including the buffer pH and EOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Parameters of the linear regression analysis are summarized in Table 2. The values of LOD found in the present study are comparable with those reported for low-molecular weight species in untreated urine with direct UV detection [27,28].…”
Section: Determination Of 3mh and 1mh In A Model Aqueous Mixture And supporting
confidence: 93%
“…Parameters of the linear regression analysis are summarized in Table 2. The values of LOD found in the present study are comparable with those reported for low-molecular weight species in untreated urine with direct UV detection [27,28].…”
Section: Determination Of 3mh and 1mh In A Model Aqueous Mixture And supporting
confidence: 93%
“…1). This can be attributed to the migration direction of As species being the same as that of the EOF, and resulted from dynamic modification of the fused-silica surface with TTAB [33,34,35,36]. Consequently, As(V) with a higher mobility appeared prior to As(III) having a lower mobility.…”
Section: Separation Of As Species By Counter-eof and Co-eof Czementioning
confidence: 81%
“…To achieve fast separation, co-EOF mode is frequently used for the separation of anions by addition of cationic surfactant such as TTAB, which results in a faster migration as the anionic solutes co-migrate with the EOF [33,34,35,36]. Since co-EOF migration in alkaline electrolyte was needed to achieve the complete separation of As species with different mobility, it was necessary to find a suitable buffer pH in co-EOF mode for the separation of target As species.…”
Section: Separation Of As Species By Counter-eof and Co-eof Czementioning
confidence: 99%
“…1, the observed mobility of anions increased with increasing electrolyte pH. As both the EOF and effective mobility of the anion increased with increasing electrolyte pH, this led to an increase the mobility of the anions [23,24,25]. However, the best resolution between Cl -and I -was achieved at pH 8.0, and this pH was therefore used for all further experiments.…”
Section: Separation Conditionsmentioning
confidence: 85%
“…Separation selectivity depends on the mobility of an anion and the EOF, which is related to electrolyte pH and the type and concentration of EOF modifier [23,24,25,26]. The influence of electrolyte pH on the mobility of anions was tested using an electrolyte containing 20 mmol L -1 NaH 2 PO 4 and 20 mmol L -1 TMAOH.…”
Section: Separation Conditionsmentioning
confidence: 99%